Participant Perceptions of Facilitators and Barriers to Adherence in a Digital Mental Health Intervention for a Nonclinical Cohort: Content Analysis - Renfrew, Melanie Elise; Morton, Darren Peter; Northcote, Maria; Morton, Jason Kyle; Hinze, Jason Scott; Przybylko, Geraldine (JMIR Publications, 2021)
BackgroundDigital mental health promotion interventions (MHPIs) present a scalable opportunity to attenuate the risk of mental health distress among nonclinical cohorts. However, adherence is frequently suboptimal, and little is known about participants' perspectives concerning facilitators and barriers to adherence in community-based settings. ObjectiveThis study aimed to examine participants' perceptions of facilitators and barriers to adherence in a web- and mobile app-based MHPI for a nonclinical cohort. MethodsThis qualitative study used inductive, reflexive thematic analysis to explore free-text responses in a postintervention evaluation of a 10-week digital MHPI. The intervention was administered using a web and mobile app from September to December 2018. Participants (N=320) were Australian and New Zealand members of a faith-based organization who self-selected into the study, owned a mobile phone with messaging capability, had an email address and internet access, were fluent in English, provided informed consent, and gave permission for their data to be used for research. The postintervention questionnaire elicited participants' perceptions of facilitators and barriers to adherence during the intervention period. ResultsKey factors that facilitated adherence were engaging content, time availability and management, ease of accessibility, easy or enjoyable practical challenges, high perceived value, and personal motivation to complete the intervention. The primary perceived barrier to adherence was the participants' lack of time. Other barriers included completing and recording practical activities, length of video content, technical difficulties, and a combination of personal factors. ConclusionsTime scarcity was the foremost issue for the nonclinical cohort engaged in this digital MHPI. Program developers should streamline digital interventions to minimize the time investment for participants. This may include condensed content, optimization of intuitive web and app design, simplified recording of activities, and greater participant autonomy in choosing optional features. Nonetheless, participants identified a multiplicity of other interindividual factors that facilitated or inhibited adherence.